The Events Of 1991-1992 December-January And Kutaisi - Sharashenidze, Shalva (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
The subject matter of the article is to restore the events that took part in Kutaisi in 1991-1992 based on the materials of the local press and Kutaisi City Council Extraordinary Sessions. According to the newspaper Kutaisi, edition of December 24, 1991huge protest rally took place at Davit Agmashenebeli square near the local authority building. From the last days of December communication with the central government thoroughly suspended. Thus, the local press was unable to publish the recent affairs held in the central part of the state. It generally relied on the verbal stories told by people travelled from Tbilisi. The local authority of the Imereti region often held mass manifestations to destroy the informational vacuum and give information to Imereti residents. Fortunately, despite the difficult situation of Kutaisi and different civil positions among the population, Kutaisi survived from bloody battle. Kutaisi’s local authority of that time showed political correctness in its motivation since it managed to prevent the distinct positioning towards the events held in the capital of the country. It took the right measures to avoid the armed conflict in Kutaisi. Thus, studying the tragic affairs of 1991-1992 on the base of the materials of local press and Kutaisi City Council Extraordinary Sessions clarifies that despite the hard socio-economic and political situation in the country and influence of the civil positions Imereti local government managed to avoid the escalation of the situation and armed con.